RANCANG BANGUN BEL OTOMATIS DI STIKOM TUNAS BANGSA BERBASIS ARDUINO DILENGKAPI DENGAN OUTPUT SUARA - Fachrul Hasby; Sumarno; Zulaini Masruro Nasution (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2021)
Abstract Bell is certainly no stranger to education. In general, the bell still uses human power to ring it. It is still rare in the world of education to use an automatic bell that can work alone according to a predetermined time in the teaching and learning process. The purpose of the design of automatic bells at STIKOM Tunas Bangsa Pematangsiantar is to facilitate the work of picket officers and optimize the time for teaching and learning. The work process of this tool is to input the predetermined lesson time into the Arduino Uno Microcontroller using C language in the Arduino IDE Software. After that the microcontroller will read the program schedule hours that have been inputted into the microcontroller. If the program inputted matches the time schedule of today's lesson hours, the bell will automatically output the output in the form of an information notification sound. This tool also has a 16x2 Keypad Shield for setting the manual in the test mode that is matched in the time of the ongoing test and automatically produces notification sound output, where the automatic bell is fully controlled with the Arduino Uno Microcontroller command and the time setting that has been set into the RTC ( Real Time Clock) as a time saver. Keywords: Arduino Uno, RTC, Keypad Shield 16x2, STIKOM Tunas Bangsa